Dose dependent but non-linear effects of alcohol on the left and right ventricle. Issue 4 (1st October 2001) - Kajander, O A; Kupari, M; Laippala, P; Savolainen, V; Pajarinen, J; Penttilä, A; Karhunen, P J
Abstract : OBJECTIVE: To assess how left (LV) and right ventricular (RV) size, wall thickness, and mass depend on daily alcohol consumption. Among alcoholics, most common findings have been LV hypertrophy and mild systolic or diastolic dysfunction, accompanied occasionally by ventricular dilatation resembling dilated cardiomyopathy. Although it is commonly agreed that chronic heavy alcohol use is injurious to the heart, the dose-injury relation remains a matter of dispute. DESIGN: Prospective series of 700 Finnish men aged 33–70 years who died out of hospital and underwent a medicolegal necropsy. METHODS AND RESULTS: Data on alcohol use and other risk factors were obtained from the spouse. At necropsy, a transversal slice of the heart was traced on a transparent sheet and analysed later for LV and RV cavity areas and wall thicknesses. Coronary artery stenoses were measured from silicone casts of the arteries. In analyses of all men, daily alcohol dose predicted heart weight (β = 0.17, p < 0.001) and RV cavity area (β = 0.14, p = 0.007) independent of body size, age, coronary artery disease, hypertension, diabetes, and smoking. In the subgroup of men free of significant coronary artery disease, LV area averaged (SEM) 11.0 (1.0) cm 2 in men drinking < 12 g/day, 7.7 (0.7) cm 2 in those drinking 72–180 g/day, and 10.0 (0.9) cm 2 in those drinking > 180 g/day (p = 0.054). Very heavy drinking (> 180 g/day) was associated with an increase in RV cavity area (p = 0.005). CONCLUSIONS: The effects of alcohol on the heart in middle aged men are dose dependent but partly non-linear. In the absence of coronary artery disease, LV size shows a U shaped reduction with increasing daily alcohol use accompanied by an increase in RV size with very heavy drinking. These findings question the idea of progressive LV dilatation with increasing alcohol consumption among male victims of sudden death.